Preparation and Characterizations of Hydroxyapatite Substituted Boron Cement - Boonphayak, Piyanan; Khansumled, Sirikarn; Pinmanee, Adisorn; Phromduang, Supakit (Asian Health, Science and Technology Reports, 2018)
The aim of this research is studying the produce boron substitution into hydroxyapatite (20BHA) cement powder and investigate the effect of citric acid on the compressive strength of new cement. 20BHA cement powder was synthesized by the co-precipitation method at room temperature. Phase and chemical structure of 20BHA powder were confirmed by X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FT-IR). The morphology in the cements was confirmed by scanning electron microscope (SEM). The effects of adding citric acid to 20BHA powder was found to have a significant effect on the compressive strength properties of cement. Increasing the concentration of citric acid in 20BHA powder was found to have an effect on the large compressive strength.